Rare Infundibular Tumors: Clinical Presentation, Imaging Findings, and the Role of Endoscopic Endonasal Surgery in Their Management - Koutourousiou, Maria; Gardner, Paul A.; Kofler, Julia K.; Fernandez-Miranda, Juan C.; Snyderman, Carl H.; Lunsford, L. Dade (Journal of Neurological Surgery Part B: Skull Base, 2013)
Background The spectrum of infundibular lesions is broad and distinct from sellar pathologies. In many cases, histology is needed to establish the correct diagnosis and determine the treatment approach.Methods Medical files of eight patients with distinct infundibular tumors were reviewed. Histopathologically confirmed diagnosis included three pituicytomas, three granular cell tumors, and two pilocytic astrocytomas.Results Patients shared similar imaging findings and clinical symptoms, including visual impairment (n = 5), hypopituitarism (n = 4), and headache (n = 4); one patient presented with disseminated disease and symptoms from spinal metastases. All the pituicytomas, two granular cell tumors, and one infundibular pilocytic astrocytoma case underwent endoscopic endonasal surgery; gross total resection was achieved in five patients, three developed postoperative diabetes insipidus, and two developed hypopituitarism. No recurrences were observed. One granular cell tumor patient was treated with gamma-knife radiosurgery after stereotactic biopsy; the tumor remained stable in size for over 9 years. The infundibular pilocytic astrocytoma patient who presented with spinal metastases received radiotherapy and systemic chemotherapy. The overall mean follow-up period was 25.1 months.Conclusion Infundibular tumors are rare entities that represent a diagnostic challenge. Histopathological examination is essential for definitive diagnosis. Surgery, radiation therapy, and chemotherapy all have a role in the management of these tumors.
Keywords: endoscopic endonasal approach; granular cell tumor; pilocytic astrocytoma; pituicytoma; radiation therapy